2022
DOI: 10.3389/fnut.2022.930883
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gut microbiota: The effects of a fruits and vegetables supplement

Abstract: The consumption of an optimal amount of fruits and vegetables is known to improve physical fitness and physiological body functions. Healthy eating habits, including intake of fruits and vegetables, can modify gut microbiota. This study aimed to demonstrate the effectiveness of a formulated fruit and vegetable supplement (FVS) in modulating the antioxidant capacity and the gut microbiota composition. We enrolled 30 healthy volunteer subjects, matched for age, gender, BMI, and smoking habits, and randomized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Specifically, an intake of 0.2 servings per day of green leafy vegetables reduced the risk for type 2 diabetes by 13% [284], with similar findings in another meta-analysis showing risk reduction of 14% [285]. Changes in microbial shifts after consumption of fruits and vegetables have also been described with study findings showing decreased abundance of the Lachnospiraceae family, including Ruminococcus, and increased concentrations of Faecalibacterium and Lactobacillus [288]. Further metagenomic sequencing studies combining two large human cohorts have shown changes that include increased abundance of Faecalibacterium prausnitzii, Akkermansia muciniphila, Ruminococcaceae, Clostridiales, and Acidaminococcus and with decrease in the abundance of Fusobacterium [289].…”
Section: Fruits and Vegetablessupporting
confidence: 56%
“…Specifically, an intake of 0.2 servings per day of green leafy vegetables reduced the risk for type 2 diabetes by 13% [284], with similar findings in another meta-analysis showing risk reduction of 14% [285]. Changes in microbial shifts after consumption of fruits and vegetables have also been described with study findings showing decreased abundance of the Lachnospiraceae family, including Ruminococcus, and increased concentrations of Faecalibacterium and Lactobacillus [288]. Further metagenomic sequencing studies combining two large human cohorts have shown changes that include increased abundance of Faecalibacterium prausnitzii, Akkermansia muciniphila, Ruminococcaceae, Clostridiales, and Acidaminococcus and with decrease in the abundance of Fusobacterium [289].…”
Section: Fruits and Vegetablessupporting
confidence: 56%
“…In the HMP2 cohort however, the correlations were generally stronger than the ones observed in the UKBB, which is not surprising considering the well-established bidirectional relationship between the gut microbiome and diet. 108 , 109 , 110 , 111 Further, there were only a few consistent diet-metabolite associations shared between the diseased and non-diseased groups of the HMP2 cohort among the top 20 metabolites, and the most prominent are currently not confirmed in literature (e.g., NMPC with soft drinks, and hydroxycotinine with beans). Further, differences across both groups was much more numerous among the fecal metabolites.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies evaluated polyphenols as part of a whole food, which included fibers naturally present in the food [ 35 ]. Our study evaluated the polyphenols and fiber blends both separately and in combination and revealed that the PPFB blend provided an additive positive impact on select taxa when mixing the two blends together in vitro relative to the blends independently.…”
Section: Discussionmentioning
confidence: 99%